Heterosis and Inbreeding Depression for fruit yield and its components in Brinjal (Solanum melongena L.) - Sao, Abhinav; Mehta, Nandan (Vegetable Science, 2011)
Brinjal is one of the major vegetable crops grown in whole India. It is most widely grown vegetable crop in Asian countries, especially in India, China, Philippines and Japan. The first generation hybrids offer several advantages such as earliness, uniformity and increased yield. To boost the productivity the trend has been in the direction evolving hybrids for exploiting heterosis.